Academic libraries in Pangasinan implications to the Private Higher Education (PHE) tentative library standards - Nera, Corazon M. (1978)
The purpose of this study was threefold: first, to present a better picture of the state of academic libraries in Pangasinan; second, to evaluate the existing library resources against the Tentative Library Standards for Private Higher Education; and third, to formulate program/project recommendations by which these libraries could, within their financial means, arrive at these standards within a reasonable time. The major areas of the programs studied were: a) objectives; b) administration; c) finance; d) collection and organization of materials; e) staff; f) services; and g) facilities.